Patients’ Recall of Diagnostic and Treatment Information Improves with Use of the Pain Explanation and Treatment Diagram in an Outpatient Chronic Pain Clinic - Hillel M Finestone; Matthew M Yanni; Catherine J Dalzell (Pain Research and Management)
Educating patients about their condition and treatment plan is an essential component of successful treatment. Patients need to understand their condition, recall treatment suggestions and comply with the treatment protocol. Unfortunately, the method of patient education most commonly used by physicians is verbal teaching and discussion, which leads to poor patient recall. The authors of this article developed the Pain Explanation and Treatment Diagram, a worksheet that the clinician completes with the patient during their first consultation to function as a record of their diagnosis, pain risk factors and an action plan for when pain occurs. In this study, patient recall, among other variables, was assessed as a function of time since first appointment.